Karakteristik Penyakit Morbus Hansen - A. Nadia sulistia ningsih; Sri Vitayani; Solecha setiawati (2024)
Morbus Hansen (MH), also known as leprosy, is an infectious disease that causes health problems worldwide. Morbus hansen is a chronic infection that primarily affects the skin and peripheral nervous system. The causative germ is Mycobacterium Leprae which is a rod-shaped, acidic, obligate intracellular bacterium that cannot be cultured in artificial media. The risk of disability can be influenced by several factors, including the type of leprosy, duration of disease, number of nerves affected, onset of leprosy reactions, gender, age, type of treatment, socioeconomic factors, education, ethnicity, occupation, and the way leprosy cases are discovered. Objective: This literature review aims to determine the characteristics of morbus hansen disease. Methods : The method used is literature review with Narrative Review design. Results : The results obtained in this literature are that there are 20 articles obtained with restrictions from 2020 - 2024 and in-depth analysis of the strengths and limitations of each article regarding the characteristics of morbus hansen disease, 20 articles mention the characteristics of morbus hansen disease. the most dominant characteristics of morbus hansen disease in this literature review are age and type of morbus hansen, followed by gender. Although there are several other characteristics such as clinical symptoms and predilection.